Experimental characterization of a short electrical mobility spectrometer for aerosol size classification - Intra P. (2014)
A prototype of a short column electrical mobility spectrometer (EMS) for size measurement of aerosol particle was design, constructed, and experimentally characterized. The short EMS consists of a particle charger, a size classifier column, and a multi-channel electrometer. Its particle size resolution is derived from a 10 channel electrometer detector. The short EMS is capable of size measurements in the range between 10 nm to 1,000 nm with a time response of about 50 s for full up and down scan. Particle number concentration in which the short EMS can measure ranges from 1011 to 1013 particles/m3. The operating flow rate of the short EMS is set for the aerosol flow rate of 1.0-2.0 l/min and the sheath air flow rate fixed at 10.0 l/min. The inner electrode voltage of the classifier can be varied between 500-3,000 VDC. The short EMS operates at sub-atmospheric pressure, typically at 526 mbar. Validation of the short EMS performance was performed against a scanning electron microscope (SEM). Good agreements were obtained from comparison between sizes determined from the short EMS classifier and the SEM analysis. Signal current from the detector was also analyzed to give rise to number concentration of particles. Experimental results obtained appeared to agree well with the theoretical predictions. © 2009 Korean Institute of Chemical Engineers, Seoul, Korea.